Multiferroic interfaces in bismuth ferrite composite fibers grown by laser floating zone technique - Figueiras, F. G.
In this work we explore the formation of enhanced multiferroic interfaces in bismuth ferrite crystalline fibers grown by laser floating zone technique. An underlying mechanism of self-segregation during the fibers growth process enables to establish a textured microstructure of a dominant BiFeO3 phase bordered by the presence of Bi25FeO40 secondary phase. The crystallites c axis of the BiFeO3 phase shows a preferential orientation along the longitudinal axis of the fibers, together with grain boundaries that also present a significant alignment with the same direction. These features induce a systematic disturbance of the antiferromagnetic structure of the BiFeO3 phase at the interfaces with the Bi25FeO40 diamagnetic phase. The structural anisotropy confirmed by High Resolution X-ray diffraction and scanning electron microscopy images is also manifested in the magnetic properties of the fibers, which reveal an enhanced susceptibility response in comparison to the conventional BiFeO3 phase diagram. (C) 2015 Elsevier Ltd. All rights reserved.